Proposing strategies to address the challenges emerging from recruitment and acquiring talent- a study on Trust Bank PLC - Navid, Mashnoor (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2024.